The Structure and Content of Online Child Exploitation Networks - Bouchard, Martin (2010)
The emergence of the Internet has provided people with the ability to find and communicate with others of common interests. Unfortunately, those involved in the practices of child exploitation have also received the same benefits. Although law enforcement continues its efforts to shut down websites dedicated to child exploitation, the problem remains uncurbed. Despite this, law enforcement has yet to examine these websites as a network and determine their structure, stability and susceptibleness to attack. We extract the structure and features of four online child exploitation networks using a custom-written webpage crawler. Social network analysis is then applied with the purpose of finding key players – websites whose removal would result in the greatest fragmentation of the network and largest loss of hardcore material. Our results indicate that websites do not link based on the hardcore content of the target website; however, blogs do contain more hardcore content per page than non-blog websites